CEOP-21 versus CEOP-14 chemotherapy with or without rituximab for the first-line treatment of patients with aggressive lymphomas: Results of the HE22A99 trial of the hellenic cooperative oncology group - Economopoulos, T.; Psyrri, A.; Dimopoulos, M.A.; Kalogera-Fountzila, A.; N. Pavlidis; Tsatalas, C.; Nikolaides, C.; Mellou, S.; Xiros, N.; Fountzilas, G. (Cancer Journal, 2007)
Background: In this study we investigated whether administering CEOP (cyclophosphamide, epirubicin, vincristine [Oncovin], and prednisone) every 2 weeks (CEOP-14) instead of every 3 weeks (the standard CEOP-21 regimen) improves outcomes in patients with previously untreated aggressive lymphomas. In a secondary analysis we evaluated the impact of adding rituximab to CEOP-14/CEOP-21 chemotherapy. Study Design: The trial opened in March 1999, and patients were randomly assigned to either CEOP-14 or CEOP-21. All patients enrolled from May 2002 onward received rituximab with each chemotherapy cycle, and those attaining a complete response received rituximab consolidation. Results: Complete and overall response rates in the CEOP-21 ± rituximab (N ≤ 114) and CEOP-14 ± rituximab (N ≤ 103) arms were similar, as were the overall survival (P ≤ 0.769) and time to progression distributions (P ≤ 0.969). Rituximab was shown to have a beneficial effect both on the overall survival and on the time to progression. Conclusions: Thus far, no significant improvement in outcome has been demonstrated with CEOP-14 ± rituximab versus CEOP-21 ± rituximab. However, with addition of rituximab to CEOP-21/CEOP-14, significant improvements in time to progression and overall survival were achieved. © 2007 by Lippincott Williams & Wilkins.
Keywords: Aggressive non-Hodgkin lymphoma; CEOP; Doseintensification; Overall survival; rituximab